The History of Tom Jones - A Foundling a BBC-Production Based on the Novel by Henry Fielding - Hüseyin, Metin; Forshaw, Cinders; Beesley, Max; Morton, Samantha; Blessed, Brian (BBC Worldwide, 2006)
When "Tom Jones" first saw publication, it was an instant controversy. Fielding pushed the edge of the social acceptability envelope ‘til it completely collapsed. The book’s frank sexuality and rakish protagonist was simultaneously exactly what the public wanted, and exactly what they couldn’t admit they wanted. The moral and ethical dichotomy of the age’s rigid social mores and their near-bottomless appetite for tales of debauchery had been distilled by Fielding into his history of a bastard foundling ... This BBC production of the novel captures the feel of the book perfectly, even including the author’s own digressions and narration (with Fielding played brilliantly by John Sessions) ... The production values are high throughout all aspects of the series, a given with most BBC/A&E literary adaptations. Costuming, sets, and the rest are all first-rate. In short, there’s not likely to be a better version filmed. The locations chosen for the project manage to capture perfectly Fielding's portrayal of Restoration-era rural England and the overblown ornamental look of the cities of the age. [www.needcoffee.com]
Keywords: DVD-Video